Pathways to diverse diets – a retrospective analysis of a participatory nutrition-sensitive project in Kenya - Boedecker, Julia; Lachat, Carl; Hawwash, Dana; Damme, Patrick van; Nowicki, Marisa; Termote, Céline (2021)
This study is based on a community-based participatory project, running in Kenya since 2015 and aiming to diversify diets of women and children by making use of local food biodiversity. An impact study indicated that dietary diversity of women and children increased through the project. Using a theoretical agriculture-nutrition framework, we assessed the pathways that have led to the dietary changes and identified possible secondary effects beyond nutrition. Data was gathered through ten semi-structured focus group discussions with community members engaging in the project and 5 key informant interviews with local authorities that worked with these communities during the project. Data analysis was supported by the approach of summative content analysis. Defined pathways were compared to existing and widely-used theoretical pathways from the literature. Out of the agriculture-nutrition pathways that are presented in literature, three were found in the responses: 1) food from own-production; 2) income from sale of foods produced; 3) women's empowerment through access to and control over resources. In addition, we identified a first pathway based on the spreading and implementation of agricultural knowledge and a second pathway that was based on saved time and money due to decreased doctor’s visits through improved health. Beyond nutritional benefits, male and female respondents reported aspects of increased empowerment and harmony in the household. Our pathway analysis provides qualitative evidence on the impact of the community-led agriculture-nutrition project on increased dietary diversity for women and young children. If done more systematically, pathway analysis in nutrition-sensitive agricultural projects could increase our understanding on how interventions improve nutrition. MethodologyWe collected qualitative data because it has the potential to assess individual behavior and allows keeping a broader scientific scope to also investigate unintended effects of an intervention. Data was gathered through ten semi-structured focus group discussions with community members engaging in the project and 5 key informant interviews with local authorities that worked with these communities during the project. Gender disaggregation during data collection and analysis has enabled interpretation regarding gender equality and women empowerment aspects. Transcripts were analyzed by two researchers. They applied the approach of summative content analysis. Defined pathways were compared to existing and widely-used theoretical pathways from the literature. Also, unintended secondary effects of the intervention were investigated.